2015
DOI: 10.1038/bjc.2015.333
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alcohol drinking on gastric cancer development according to Helicobacter pylori infection status

Abstract: Background:Helicobacter pylori are major carcinogen of gastric cancer, but the associations among gastric cancer, H. pylori infection status, and alcohol consumption are not fully described. This study aimed to clarify how H. pylori infection status affects the association between alcohol consumption and gastric cancer risk.Methods:We selected 949 case–cohort participants from the 18 863 Korean Multi-center Cancer Cohort (KMCC) populations. Gastric cancer incidence inside and outside of the subcohort were 12 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
0
40
1
2
Order By: Relevance
“…Similarly, in a Korean cohort study no significant association could be demonstrated between drinking alcohol and the development of stomach cancer among infected residents. Neither the number of years of alcohol drinking, nor the drinking frequency, nor the average dose were associated with stomach cancer compared to infected alcohol abstainers after adjustments for age, sex, body mass index, educational level, and smoking status …”
Section: Resultsmentioning
confidence: 89%
“…Similarly, in a Korean cohort study no significant association could be demonstrated between drinking alcohol and the development of stomach cancer among infected residents. Neither the number of years of alcohol drinking, nor the drinking frequency, nor the average dose were associated with stomach cancer compared to infected alcohol abstainers after adjustments for age, sex, body mass index, educational level, and smoking status …”
Section: Resultsmentioning
confidence: 89%
“…Nevertheless, other studies have found similar intriguing inverse associations 49,50 . In a study using gastric cancer as an endpoint, it was concluded that the absence (among H. pylori ‐positive individuals) and the presence (among H. pylori ‐negative individuals) of an association between alcohol intake and gastric cancer would suggest that alcohol might have an antimicrobial effect on H. pylori 51 . However, the opposite might also be true; individuals infected with H. pylori might be less inclined to consume alcohol due to a lower tolerance to alcohol in a stomach with chronic inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore; smoking and low fruit and vegetable intake are also risk factors for both cancer types, in addition to alcohol use for oesophagus cancer . Heavy alcohol use and binge drinking has been found to increase the risk of gastric cancer in a population relatively unaffected by H. pylori . In Mongolia, almost 50% of males and 27% of females have been recently reported as current drinkers of alcohol; the prevalence of binge drinking was about 40% in men, 2.5 times more than that of women .…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] Heavy alcohol use and binge drinking has been found to increase the risk of gastric cancer in a population relatively unaffected by H. pylori. 41 In Mongolia, almost 50% of males and 27% of females have been recently reported as current drinkers of alcohol; the prevalence of binge drinking was about 40% in men, 2.5 times more than that of women. 42 Smoking prevalence is much higher in men (43%) compared to women (5%), while 36% to 43% of the population was exposed to second-hand smoke either at work or home.…”
Section: Cancer Epidemiologymentioning
confidence: 99%